2019
DOI: 10.1182/bloodadvances.2019000717
|View full text |Cite
|
Sign up to set email alerts
|

Durable preservation of antiviral antibodies after CD19-directed chimeric antigen receptor T-cell immunotherapy

Abstract: Key Points Virus-specific IgG levels were stable for up to 1 year after CD19-CARTx in adults with durable complete remission. Preexisting humoral immunity may be preserved in adult recipients of CD19-CARTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 50 publications
4
61
0
Order By: Relevance
“…The retained antibody repertoire could represent a core stable LLPC repertoire (~90%), and the 10% that was lost could represent a transient repertoire derived from IgG-secreting B cells and plasmablasts. This result is consistent with previous studies that showed no effect of immunosuppressive therapy, such as B celldepleting anti-CD19 or anti-CD20 treatment, on retention of the majority of the antibody repertoire (17,19,21,22). Therefore, measles is associated with greater loss of antibodymediated epitope recognition than can be explained by ablation of B cells, suggesting a direct effect on the LLPC compartment.…”
Section: Measles Modulates the Diversity Of The Antibody Repertoire Asupporting
confidence: 92%
See 1 more Smart Citation
“…The retained antibody repertoire could represent a core stable LLPC repertoire (~90%), and the 10% that was lost could represent a transient repertoire derived from IgG-secreting B cells and plasmablasts. This result is consistent with previous studies that showed no effect of immunosuppressive therapy, such as B celldepleting anti-CD19 or anti-CD20 treatment, on retention of the majority of the antibody repertoire (17,19,21,22). Therefore, measles is associated with greater loss of antibodymediated epitope recognition than can be explained by ablation of B cells, suggesting a direct effect on the LLPC compartment.…”
Section: Measles Modulates the Diversity Of The Antibody Repertoire Asupporting
confidence: 92%
“…Antibodies are thought to better represent long-lived humoral memory (18,20). Most antibodies in the peripheral blood are produced by bone marrow long-lived plasma cells (LLPCs) and are impervious to disruptions in peripheral memory cells (17)(18)(19)(20)(21)(22). Changes in pathogen-specific antibodies measured in the peripheral blood reflect changes in the long-lived permanent memory repertoire.…”
mentioning
confidence: 99%
“…However, there are data showing persistent long-lived plasma cells after CAR T cell therapy 22 . In addition, Hill and colleagues recently demonstrated preserved anti-viral humoral immune response in patients treated with CD19 CAR T cells 23 . The authors reported sustained anti-measle IgG level independent of the total IgG level in 95% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 12 Because long-lived plasma cells are not a direct target of CD19 + CAR-T cells, the humoral immunity may be preserved. 16 In the absence of data, we recommend complete vaccinations according to the patient's age and seroprotection status.…”
Section: Icans Managementmentioning
confidence: 99%